PENGARUH BERMAIN PERAN TERHADAP KECERDASAN INTERPERSONAL ANAK DI KOBER SERUNI NAGRAK KABUPATEN SUKABUMI - Ajeng Teni; Lia Trinuari; Dede Ridwan (Jurnal El-Audi, 2023)
Early Childhood Education is a form of education that focuses on laying the foundation for physical growth and development (fine and gross motor coordination), intelligence (thinking power, creativity, emotional intelligence, spiritual intelligence), socio-emotional attitudes and behavior. and religion), language and communication, in accordance with the uniqueness and stages of development that are passed by early childhood. The formulation of the problem in this study is that the discussion in this study is more focused, so the authors limit this problem to: Is there an interaction effect between role playing games on interpersonal intelligence? This study aims to analyze the interaction effect of traditional anjang-anjangan games on children's interpersonal intelligence at KOBER Seruni Nagrak. In this study, the method used is the experimental method. As for the technique of collecting data in this research is through documentation techniques, observation and check lists. The data analysis technique of this research is through data normality test, homogeneity test. Based on the results of hypothesis testing obtained through research on the effect of role-playing games on children's interpersonal intelligence at KOBER Seruni Nagrak, it was found that the average value of student learning outcomes in the experimental group was higher than the average interpersonal intelligence of children in the control group because they used toy games. role. Based on the results of this study it can be concluded that the results of the paired sample t-test, the average between pretest and posttest in the control class is -1.667 with a standard deviation of 11.178 and t-obtained is -0.577. At a significant level of 0.05 degrees of freedom 14. It can be seen that the t-obtained value is lower than the t-table. It can be concluded that there is no effect of using pictures on children's interpersonal intelligence in KOBER Seruni Nagrak.